Le genre au prisme de l’archéologie : quelques réflexions autour de la « dame de Vix » - Sandra Péré-Noguès (Les Cahiers de Framespa)
If the female burial Vix (Burgundy), one of the largest collections funerals of the late Iron Age, first aroused the interest of archaeologists, few have discussed its analysis through the gender. In light of recent studies, we can consider how relations could be discussed between social status and gender, between gender and power.